2008
DOI: 10.1002/ana.21228
|View full text |Cite
|
Sign up to set email alerts
|

Cortical connectivity after subcortical stroke assessed with functional magnetic resonance imaging

Abstract: Objective: This study aimed at identifying the impact of subcortical stroke on the interaction of cortical motor areas within and across hemispheres during the generation of voluntary hand movements. Methods: Twelve subacute stroke patients with a subcortical ischemic lesion and 12 age-matched control subjects were scanned using 3-Tesla functional magnetic resonance imaging. Subjects performed visually paced hand movements with their left, right, or both hands. Changes of effective connectivity among a bilater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

50
437
7
19

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 524 publications
(513 citation statements)
references
References 35 publications
50
437
7
19
Order By: Relevance
“…Alterations in down-stream, higher cortical areas, not directly affected by the lesion, were already demonstrated by gene expression studies [42] and single-unit recordings in animal models [43,44], as well as MEG [45] and fMRI studies in humans [20,[46][47][48][49][50][51][52]. This is in line with findings from motor [53,54] and attentional systems [55] where lesion-induced network modifications have been increasingly recognized and appreciated. However, the behavioral correlates of network alterations are still poorly understood in all systems.…”
Section: Global Effect Of Visual System Lesionssupporting
confidence: 77%
“…Alterations in down-stream, higher cortical areas, not directly affected by the lesion, were already demonstrated by gene expression studies [42] and single-unit recordings in animal models [43,44], as well as MEG [45] and fMRI studies in humans [20,[46][47][48][49][50][51][52]. This is in line with findings from motor [53,54] and attentional systems [55] where lesion-induced network modifications have been increasingly recognized and appreciated. However, the behavioral correlates of network alterations are still poorly understood in all systems.…”
Section: Global Effect Of Visual System Lesionssupporting
confidence: 77%
“…We demonstrate state-dependent and timing-dependent, topographically specific bidirectional Hebbian-like associative plasticity in the SMA-M1 network. Recent studies showed a significant role of effective coupling of neuronal activity in the SMA-M1 network for motor outcome in patients after stroke (Grefkes et al, 2008(Grefkes et al, , 2010. In this context, the present study may signify therapeutic potential to support purposeful modification of coupling in the SMA-M1 network in neurological disorders in which dysfunction of this network contributes to the clinical impairment.…”
Section: Introductionmentioning
confidence: 53%
“…The dynamic causal modeling (DCM) is a hypothesis-driven approach, which was specifically designed to evaluate the intrinsic and task-dependent influences that a particular brain area exerts over the activity of another area (Friston, 2003;Stephan et al, 2004;Grefkes et al, 2008). The DCM treats the brain as a deterministic system, in which external input causes changes in neural activity that, in turn, lead to changes in the fMRI signal.…”
Section: Methodological Considerations For the Evaluation Of Effectivmentioning
confidence: 99%